The Flare Up of Catastrophic Antiphospholipid Syndrome: a Report of an Immunosuppressive Withdrawal-Induced Case - Mortazavimoghaddam, Sayyed Gholamreza (Shiraz University of Medical Sciences, 2011)
Antiphospholipid syndrome (APS) is a systemic disease that causes venous and arterial thrombosis in virtually any organ. Sometimes it is complicated into pulmonary infarction and cavitation, pulmonary hypertension, and catastrophic course with high morbidity and mortality. The present case is a 35-year-old woman with one episode of postpartum deep veins thrombosis (DVT) 12 years earlier and the second one after the second labor two years later. In spite of usual therapy for each episode of DVT, the condition had progressed into severe pulmonary hypertension. The diagnosis of primary APL syndrome was confirmed four years ago. She had been on warfarin, low dose of steroid, and azathioprine since the diagnosis of APL syndrome. After one year treatment with steroid and azathiprine the patient showed progressive well being; however, because of hyperglycemia the steroid tapered and discontinued. She had several attacks of paroxismal atrial tachycardia in the last year. On the last time, she presented with severe dyspnea, hemoptesis, and lower limbs edema. Chest radiography and Lung CT scan demonsterated the presence of lung cavitations. Because of high suspicious for fungal pulmonary infection, azathioprine was also discontinued. However, constellation renal failure, hemodynamic instability, and confusion caused the patient to succumb to death. The definite diagnosis of lung cavitations was not obtained.